Living Architecture: Re-imagining Vernacularity in Southeast Asia and Oceania. Issue 1 (2nd January 2020) - Vellinga, Marcel
ABSTRACT: Southeast Asia and Oceania have a long tradition of outstanding scholarship that studies the rich and diverse vernacular architectural heritage of the region. Up until the early twenty-first century, this work tended to focus on traditional forms of vernacular architecture, emphasising their regional distinctiveness and analysing the ways in which they reflected social and cultural structures. However, recent decades have seen rapid and fundamental social, economic, and environmental changes in the region that require new perspectives on the design, use, and meaning of vernacular architecture. Processes like population growth, urbanisation, globalisation, climate change, migration, natural disasters, conflicts, and the internationalisation and commercialisation of architectural practice have exerted increasing pressure on vernacular architectural traditions. In recent decades more dynamic and active approaches to the study of vernacular architecture have emerged that attempt to challenge the dichotomies inherent in earlier definitions and representations of the vernacular. Those approaches raise interesting and indeed fundamental questions about the way the vernacular architecture of the region has been represented in the past; about the validity of those representations; and ultimately about how relevant they are in the here and now. Indeed, they call into question the validity and relevance of the concept of vernacularity itself.